Gallic acid: An anticandidal compound in hydrolysable tannin extracted from the barks of Rhizophora apiculata Blume - Lim Sheh Hong, Darah Ibrahim, Jain Kassim, Suraya Sulaiman (Journal of Applied Pharmaceutical Science)
A research was conducted to study the anticandidal compound of tannin extracted from the barks of a mangrove tree, Rhizophora apiculata Blume. Tannin obtained from the barks of Rhizophora apiculata Blume was further separated into condensed and hydrolysable tannins. A strong anticandidal activity was detected in the hydrolysable tannin, which exhibited minimal inhibitory concentration (MIC) of 6.25 mg/ml, and it was found to have yeastostatic activity at lower concentration (below MIC value) and yeastocidal activity at higher concentration (more than the MIC value). Furthermore, the isolation of the bioactive compound in hydrolysable tannin that responsible for the anticandidal activity was also determined using thin layer chromatography and high-performance liquid chromatography (HPLC). The results obtained confirmed that gallic acid was the bioactive compound that plays role in inhibiting and killing the Candida albicans cells.
Keywords: Hydrolysable tannin, Rhizophora apiculata, anticandidal activity, gallic acid.